In situ investigation of phosphonate retarder interaction in oil well cements at elevated temperature and pressure conditions. Issue 11 (9th August 2020) - Kupwade‐Patil, Kunal; Boul, Peter J.; Rasner, Diana K.; Lapidus, Saul H.; Leao, Juscelino B.; Johnson, Kenneth D.; Thaemlitz, Carl J.; Büyüköztürk, Oral
Abstract: The effect of a high‐performance retarding additive in oil well cements was investigated under elevated temperature (165°C) and pressure (1000 psi) conditions via in situ synchrotron‐based X‐ray diffraction (XRD) and quasielastic neutron scattering (QENS) techniques. Under these temperature and pressure conditions, crystalline calcium silicate hydrates (C–S–H) are formed through the cement hydration process. From in situ XRD experiments, the retardation effect was observed by a change in the rate of the appearance of 11 Å tobermorites as well as a change in the rate of the α‐C2 SH generation and depletion. QENS analysis revealed that the retardation effect was related to the non‐conversion of free water to chemical and constrained water components. A high presence of free water components was attributed to a decrease in 11 Å tobermorites along with slower consumption of the quartz and portlandite phases. Furthermore, QENS results infer that the water molecules experienced confinement in the restricted pore spaces. The retarder inhibited this initial water confinement by slowing the bulk diffusion of free water in the confined region.